Nursing Care of the Pediatric Neurosurgery Patient - Cartwright, Cathy C.; Wallace, Donna C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Nursing Care of the Pediatric Neurosurgery Patient is a detailed reference for nurses and other health care providers who care for children with neurosurgical problems. The explanations of pathophysiology, anatomy, radiodiagnostic testing, and treatment options for each neurosurgical diagnosis will help to clarify the rationale behind the nursing care. Descriptions of presenting symptoms, history and findings on neurological examination will help nurses understand the neurological disorder and identify problems. Each chapter includes case studies, impact on families, patient and family education, and practice pearls. Staff and student nurses working in clinics, critical care units, pediatric units, operating rooms, post-anesthesia care units, emergency departments, and radiology departments will benefit from the information presented. Although this book is written for nurses, medical students and neurosurgery residents will also find it helpful.
Neurological Assessment of the Neonate, Infant, Child and Adolescent -- Hydrocephalus -- Craniosynostosis and Plagiocephaly -- Neural Tube Defects -- Chiari Malformation and Syringomyelia -- Tumors of the Central Nervous System -- Traumatic Brain Injury -- Spine -- Cerebrovascular Disease -- Surgical Management of Epilepsy -- Surgical Management of Spasticity -- Infections of the Central Nervous System -- Perioperative Care -- Transition Care Into Adulthood.
Keywords: Medicine; Neurology; Neurosurgery; Nursing; Pediatrics; Medicine & Public Health; Neurosurgery; Nursing Management/Nursing Research; Pediatrics; Neurology